A failure model for the analysis of cross-ply Non-Crimp Fabric (NCF) composites under in-plane loading: Experimental & numerical study. (August 2022) - Gouskos, D.; Iannucci, L.
Abstract: In the present work, a set of physically-based failure criteria are applied to a cross-ply Non-Crimp Fabric (NCF) composite. The proposed criteria account for the stitch reinforcement and the induced in- and out-of-plane fibre misalignment. A distinction between matrix and fibre failures in tension and compression is introduced, while the in-plane shear non-linear response is directly incorporated to the model as well. The constitutive model is associated with an energy-based damage mechanics method, which consists of five in-plane damage variables per layer level. Within this study, a novel approach to obtain the effective longitudinal stiffness of the composite, as a function of the in- and out-of-plane misalignment, is described. An experimental study characterises the internal structure and the mechanical response of the composite in tension, compression, in-plane shear and Mode I & II interlaminar fractures. In this paper, validation examples for the failure criteria, implemented in Abaqus/Explicit as a VUMAT subroutine, are presented. Tensile, in-plane shear and compressive responses are modelled at a coupon level with continuum shell elements and correlate well with the experimental data. Fibre misalignment, mainly out-of-plane, had a strong influence on the compressive modulus and strength of the composite. Highlights: In an NCF layer, in-plane fibre misalignment is lower than out-of-plane by app. 48%. In- & out-of-plane fibre misalignments combined, reduce exponentially E11 & XC . The novel KD factor captured E11 degradation with a 2.5–4.5% deviation against tests. The new terms of the fibre compression criterion contribute by 20% to XC prediction. Average misalignment models agree well with test results for tension & tension-shear. The proposed constitutive model is able to predict the failure modes of NCF coupons.